Screening of antagonistic bacteria for biocontrol activities against Fusarium oxysporum and Ganoderma boninense - Mat Nawi, Nurul Ashiqin (2013)
Ganoderma boninense is a fungus that is pathogenic on oil palms causing basal stem rot and most destructive disease of oil palm in South-East Asia. Meanwhile, Fusarium oxysporum is a causal agent of Fusarium wilt which affects a broad range of plants including black pepper, cucumber, banana and tomato. This study determined the potential of antagonistic bacteria that inhibited againts G.boninense and F.oxysporum growth. Five types of bacteria isolates, BLH, B38, B40, B41 and B43 were used for screening of their antagonistic activity againts G.boninense and F.oxysporum. The bacteria isolates were screened for in vitro antagonistic activity towards both fungal, G.boninense and F.oxysporum through dual culture and culture filtrate test/ diffusible antibiotic. The result showed that all of the bacteria isolates inhibited the growth of F.oxysporum and G.boninense with percentage of inhibition radial growth (PIRG) values ranging from 47.57 to 63.78% and 38.8 to 62.0%. Isolates B43 showed highest antagonism against F.oxysporum and G.boninense mycelia with 83.19 and 97.37% in culture filtrate test. The antifungal activities apparently involved the secretion diffusible bioactive compounds. Information obtained from this study showe the potential of B43 as biocontrol agent against G. boninense and F.oxysporum. It might be an economical as well as environmental save way to suppress the diseases.